2018
DOI: 10.1038/s41419-017-0233-y
|View full text |Cite
|
Sign up to set email alerts
|

The MiR-135b–BMAL1–YY1 loop disturbs pancreatic clockwork to promote tumourigenesis and chemoresistance

Abstract: Circadian disruption has been implicated in tumour development, but the underlying mechanism remains unclear. Here, we show that the molecular clockwork within malignant human pancreatic epithelium is disrupted and that this disruption is mediated by miR-135b-induced BMAL1 repression. miR-135b directly targets the BMAL1 3′-UTR and thereby disturbs the pancreatic oscillator, and the downregulation of miR-135b is essential for the realignment of the cellular clock. Asynchrony between miR-135b and BMAL1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 49 publications
6
53
0
Order By: Relevance
“…Recently, it was reported that the molecular clockwork within malignant human pancreatic epithelium disruption and resistance to GEM is mediated by miR-135b-induced BMAL1 repression. Moreover, authors found that YY1 transcriptionally activated miR-135b and formed a “miR-135b- BMAL1 -YY1” loop, which has significant predictive and prognostic value for patients with pancreatic cancer ( 159 ). PER 2 has a critical role in controlling the malignancy of cancers and also showed a mechanism regulating the resistance of oncogene-transformed PER2 m/m cells against the cytotoxicity of chemotherapeutic drugs.…”
Section: Circadian Clock Pancreatic Cancer and Therapymentioning
confidence: 99%
“…Recently, it was reported that the molecular clockwork within malignant human pancreatic epithelium disruption and resistance to GEM is mediated by miR-135b-induced BMAL1 repression. Moreover, authors found that YY1 transcriptionally activated miR-135b and formed a “miR-135b- BMAL1 -YY1” loop, which has significant predictive and prognostic value for patients with pancreatic cancer ( 159 ). PER 2 has a critical role in controlling the malignancy of cancers and also showed a mechanism regulating the resistance of oncogene-transformed PER2 m/m cells against the cytotoxicity of chemotherapeutic drugs.…”
Section: Circadian Clock Pancreatic Cancer and Therapymentioning
confidence: 99%
“…It is of interest to note that Bmal1 inhibits the induction of miR-155 via interfering with the activation of the inflammatory pathway, and miR-155 directly targets Bmal1 to control circadian inflammatory responses in macrophages [33]. In addition, miR-135b directly targets the BMAL1 3'-UTR and asynchrony between miR-135b and BMAL1 expression impairs the local circadian control in pancreatic cancer cells [34]. MiR-10a contributes to the down-regulation of the expression of Bmal1, which is involved in abnormal liver metabolism in cirrhotic liver [35].…”
Section: Interplay Of Circadian Genes and Mirnasmentioning
confidence: 99%
“…A zinc finger transcription factor, that can either repress or activate gene transcription by recruiting different cofactors. YY1 expression is increased in PDAC [245,246], higher YY1 levels are associated with oncogenic KRAS G12D status in pancreatic cancer cell lines and patient samples [245]. YY1 regulates the expression of Snail1 and VEGF, promoting EMT and angiogenesis [247,248].…”
Section: Yy1mentioning
confidence: 99%